Premios Fortabat, 1984-1999 - Alonso, Rodrigo (Fundación Amalia Lacroze de Fortabat, 2018)
"The Fortabat Prizes were key in the configuration of the Argentine art circuit between the recovery of democracy and the consolidation of the art market at the end of the 1990's. Its almost two decades of existence witnessed a time in which the expression and creativity were reestablished as unavoidable values for a society in cultural, political and institutional recomposition. In this framework, and at the initiative of Amalia Lacroze de Fortabat, this award was created with the aim of encouraging contemporary artistic production and recognizing its greatest exponents of the 1980's and 1990's." (HKB Translation) --Page 8. This exhibition represents the diversity and plurality of their plastic expressions and the legacy of some unjustly forgotten artists. Participant artists included: Ernesto Deira, María Heras Velasco Tótem, Duilio Pierri Resfalosa, Alfredo Prior, Guillermo Kuitca, Jorge Álvaro, Juan Lecuona, Eduardo Hoffman Dromedario, Juan José Cambre, Jacques Bedel Res Vitae, Oscar Páez, Raúl Lozza, Miguel Harte, Margarita Paksa
Esta publicación es el catálogo de la exhibición Premios Fortabat 1984-1999 que se realizó en la Colección de Arte Amalia Lacroze de Fortabat, 26 de octubre de 2018 / 24 de febrero de 2019 (Impressum)
Keywords: Lacroze de Fortabat, Amalia -- 1921-2012; Geschichte 1984-1999; Kunst; Kunstpreis; Argentinien; Premios Fortabat / Exhibitions; Art, Argentine / 20th century / Exhibitions; Art, Argentine; Premios Fortabat; 1900-1999; Exhibition catalogs; Ausstellungskatalog -- Colección de Arte Amalia Lacroze de Fortabat -- 26.10.2018-24.02.2019 -- Buenos Aires; Bildband